The effect of digital financial inclusion on the green economy: the case of Egypt - Doaa Salman; Doaa Ismael (Journal of Economics and Development, 2023)
Purpose – This paper aims to assess whether digital financial inclusion (DFI) supports Egypt's CO2 reduction efforts. More specifically, this paper examines the dynamics between digital finance, traditional financial inclusion (TFI) and renewable energy on carbon emission in Egypt. Design/methodology/approach – The study employed the autoregressive distributive lag (ARDL) model for Egypt over the period 1990–2020 to estimate an extended STIRPAT model for long-run linkages of DFI, traditional bank-based financial inclusion and renewable energy on carbon emissions, along with other control variables. Findings – The results showed that using digital financial services limits carbon emissions in the long run but not in the short run, indicating that Egypt is still in its early stage of digitalization (DFI < 0.5). Moreover, renewable energy proved to have a significant negative impact on carbon emissions in the long run, implying that more investments in renewable energy projects will improve environmental quality. Practical implications – The findings from this study help policymakers incorporate DFI policies into climate change adaptation strategies and execute better green growth policies that integrate DFI with energy-efficient technologies investments for a better environment. Social implications – Foster economic growth and sustinabaility. Originality/value – This study contributes to the literature by quantifying the DFI in Egypt using a two-stage principal component analysis and then examines its impact on carbon emission reduction efforts. In addition, this paper extends the research on the environment from the perspective of digital finance, making it possible to excavate more deeply into the relationship between financial inclusion and carbon emission and draw more explicit policy implications for sustainable economic growth.